The Relationship Between The Level of Emotional Intelligence and The Learning Outcomes of Physical Education Sports and Health in Public Senior High School 4 Bandung City - Bara Akmal Kusuma; Helmy Firmansyah; Carsiwan (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to determine the relationship between emotional intelligence and learning outcomes of Physical Education, Sports, and Health (PESH) in high school students. Emotional intelligence is an individual’s ability to recognize, understand, and manage their own emotions and those of others. In the context of PESH learning, emotional intelligence is thought to play an important role in supporting learning success, both in cognitive, psychomotor, and affective aspects. The research method used was a correlational survey with a quantitative approach. The sample consisted of grade X students who were selected randomly. The research instrument used an emotional intelligence questionnaire and documentation of PESH learning outcomes. The results of the analysis showed that there was a significant positive relationship between emotional intelligence and the three aspects of learning outcomes. Students with high levels of emotional intelligence tend to have a better understanding of the material, more optimal motor skills, and more positive attitudes and interests towards PESH activities. These findings indicate that strengthening emotional intelligence needs to be a concern in the learning process, especially in physical education which requires emotional involvement, social interaction, and active participation.